Owning Books and Preserving Documents in Medieval Jerusalem The Library of Burhan al-Din - Hirschler, Konrad (Edinburgh University Press, 2023)
In the late medieval period manuscripts galore circulated in private collections and in educational libraries in the cities of the Middle East. Yet very few have left a documentary trail or have survived as an easily identifiable compact corpus. Writing their histories, understanding their social settings and comprehending their intellectual profiles is therefore a challenge.This book discusses the only known private book collection from pre-Ottoman Jerusalem for which we have a trail of documents. It belonged to an otherwise unknown resident, Burhān al-Dīn; after his death, his books were sold in a public auction and the list of objects sold has survived.This list - edited and translated in this volume - shows that a humble part-time reciter of the late 14th century had almost 300 books in his house, evidence that book ownership extended beyond the elite. Based on a corpus of almost fifty documents from the Ḥaram al-sharīf collection in Jerusalem, it is also possible to get a rare insight into the social world of such an individual. Finally, the book gives a unique insight into book prices as it will make available the largest such set of data for the pre-Ottoman period.